Đánh giá của cựu sinh viên về chương trình đào tạo giáo viên môn Giáo dục công dân của Khoa Sư phạm, Trường Đại học Thủ đô Hà Nội - Nguyễn, Thị Xiêm (Tạp chí Giáo dục, 2024)
The training equation needs to be regularly evaluated to help training facilities make timely adjustments to perfect the program. One of the participants in the program evaluation is former students. The article presents the opinions of former students of the Citizen Education major of the Faculty of Education, Hanoi Capital University about the training program in the following aspects: goals and output standards of the training program; structure and content of the training program; Evaluate the quality of lecturers, staff and experts. The results show that alumni evaluation of the program is relatively good, but there are still certain limitations. This study is one of the bases (along with other evaluation subjects) for the School to adjust the training program to meet society's requirements, some of which include: adjust the general knowledge block with the number of modules and credits; supplement the number of teaching staff; use active teaching methods.